El ejército chileno y la industrialización de la guerra, 1885-1930. Revolución de la táctica de acuerdo a los paradigmas europeos - Brahm García, Enrique (Historia, 2001)
Starting from the central decades of the XIX Century a series of technical advances took place concerning the developement of fire arms wich gave the defensive a clear advantage on the tactical field. Nevertheless the strong nations faced the First World War convinced that the offensive tactics still were the strongest form of fighting, therefore originating the "holocaust" in the trenches. The present paper seeks to determine how the evolution of the European tactical thought was acknowledged before the problem created by the industrialization of the war in the Chilean army during the years of the German influence.